Assessing Gaze Patterns in Common Cosmetic Procedures With Eye-Tracking Technology. (May 2020) - Peterson, Dylan J.; Azad, Amee D.; Gkorila, Aikaterina; Patel, Ashraf A.; Boudreault, Molly S.; Nazerali, Rahim S.
Abstract : Background: Understanding the salient features that draw focus when assessing aesthetics is important for maximizing perceived outcomes. Eye-tracking technology provides an unbiased method for determining the features that draw attention when evaluating aesthetic plastic surgery. This study aimed to characterize viewing patterns of plastic surgery patients and laypeople when assessing facial cosmetic procedure images. Methods: Twenty women who previously underwent cosmetic procedures and twenty women without a history of cosmetic procedures were shown sixteen pairs of preprocedure and postprocedure images of patients who underwent laser resurfacing or lip augmentation. Image pairs were randomized to whether preprocedural or postprocedural images came first. Participants viewed each image until they decided upon an aesthetic rating (scored 1–10), while an eye-tracking device recorded participants' gaze. Results: The patient group's average ratings were 8.2% higher for preprocedural images and 13.3% higher for postprocedural images ( P < 0.05 for both). The patient group spent 20.4% less time viewing images but spent proportionally more time evaluating the relevant features of each procedure (41.7% vs 23.3%, P < 0.01), such as the vermillion border of the upper lip, labial commissure, or periorbital region ( P < 0.05 for each). For both groups, the most common site of first fixation was the nose for laser resurfacing images (26.6%) and the labial commissure for lip augmentation images (37.7%). Both groups spent more time fixated on nasolabial folds, marionette lines, and the periorbital region when viewing pre–laser resurfacing images than postprocedural images. Overall, each group had similar viewing patterns for time to first fixation on and frequency of fixations for a particular feature. Conclusions: Women who previously underwent cosmetic procedures view postprocedural images more favorably and require less time to assess images, likely related to familiarity with aesthetic procedures. These women spend more time fixated on relevant features, such as the vermillion border of the upper lip, the labial commissure, and the periorbital region, than the control group. Notably, each group spent less time focused on regions associated with wrinkles, such as the marionette and periorbital areas in post–laser resurfacing images, suggesting that the procedure reduces attention-drawing features in these areas.